INTERAKSI SOSIAL ANTARA ORANG BUGIS DAN ATOEN PAH METO: (Studi Sosiologis Di Desa Teun Baun Dan Desa Nekbaun Kecamatan Amarasi Barat Kabupaten Kupang) - Kornalius Tanesab; Jeferson Tanesab (Journal of Creative Student Research, 2023)
This study entitled Social Interaction Between Bugis and Atoen Pah Meto (Sociological Study in Teun Baun Village and Nekbaun Village, West Amarasi District, Kupang Regency). The background of this research is what are the forms and patterns of social interaction between the Bugis and Atoen Pah Meto in Teun Baun Village and Nekbaun Village? The aims of this research are 1) to know the social and economic life of the Bugis and Atoen Pah Meto people; 2) To find out the Forms and Patterns of economic social exchange, mutual social interaction such as: social closeness, cooperation; 3) management of impressions and messages, comparing the process of social exchange, mutual social interaction: cooperation, and messages and impressions that are contained in the social interactions of the Bugis and Atoen Pah Meto people in the two villages.This study uses a qualitative method with an inductive approach to the type of intrinsic case study research. The focus of this research is symbol interactionism. The techniques used are observation and interviews.The results showed 1) The social interaction between the Bugis and Atoen Pah Meto in Teun Baun Village and Nekbaun Village was very harmonious because there had never been any conflict; 2) Bugis people can still control their expenses and income from sales properly, while the Atoen Pah Meto people don't have records and they don't support each other; 3) The degree of social exchange as practiced by the Bugis and Atoen Pah Meto in terms of fulfilling the basic needs of the community is quite good.The conclusion of this research is that the trade relations of the Bugis people are far more advanced than those of the Atoen Pah Meto, why is it because the Bugis people concentrate fully on the kiosk business, on the other hand the Atoen Pah Meto people do farming and livestock as a legacy from their ancestors. The researcher's suggestion is that there is a need for cooperation in the kiosk business and trying to trust each other in carrying out a productive business.